Structural Causes of Social Inequality in Indonesia: A Critical Analysis of Justice and Policy Failure - Haura Nadine Nayla Faidza; Sholahuddin Al Ayubi (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
Social inequality in Indonesia remains a persistent issue, rooted in structural problems within economic and political systems that fail to deliver justice for all citizens. This study aims to critically examine how state economic policies, unequal wealth distribution, and limited access to public services have deepened social disparity. Using a qualitative approach, it evaluates policy shortcomings and explores the consequences of asymmetrical socioeconomic structures on distributive justice. The findings reveal that policies often favoring elite groups exacerbate inequality and restrict equitable access to education, healthcare, and employment opportunities. In addition to policy analysis, this research employs a textual and contextual study of Qur’anic verses on justice (al-‘adl, al-qisṭ) to offer an Islamic ethical perspective on social justice. The study argues that Islamic teachings advocate for a just socio-economic order and that integrating such values into policymaking could address systemic injustice. This research contributes to a more holistic understanding of inequality by bridging critical policy analysis with Qur’anic moral frameworks.